Improving Student Learning Outcomes Through Problem-Based Learning Model Assisted with Picture Media - Fauziah, Nahdiah Nur; Adi, Depict Pristine (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The purpose of this article is the researcher's goal is to understand the increase in learning studies from students in the PBL model assisted by class IV pictorial media at SDN Kawisrejo on various jobs with non-media and with media images. Because the researchers found several student barriers including: Efforts to increase the results of children's learning interest in the material of various Class IV Theme 4 jobs at SDN Kawisrejo, researchers have limitations so that problems do not spread too widely. Achievement of IPS knowledge competence focuses on: 1. Students do not actively participate in learning, 2. Students find it difficult to understand IPS material, 3. Students' thinking skills still need to be maximized 4. The reasons for the lack of learning media used by educators and the efforts that can be made and why do learning resources only come from an educator? The method used is the Classroom Action Research (CAR) method at SDN Kawisrejo. Where the increase in the results of social studies learning interest is still low and there needs to be variation from an educator to his students so that it is easy to understand and apply. Classroom action research is an activity carried out by the teacher in order to improve previous learning which is considered unsuccessful. Based on the existing data above, in the pre-stage there were 10 students who passed and 15 students who were still unsuccessful with a class average of 63.24. after the pre-stage there was a change in stage 1 where students who passed increased to 20 while students who were below average or not successful as many as 5 students had an average class value of 70.84. And in stage 2 which is the final stage which increases the results of social studies learning interest with all students completing the social studies subject matter so that learning objectives can be achieved and have maximum success.